PENDIDIKAN BERTANGGUNG JAWAB MEWUJUDKAN MASYARAKAT INDONESIA BARU - Haryanto Haryanto (Jurnal Cakrawala Pendidikan, 2001)
Tile discourse ()n tile civil society as tIle new Indonesian society Wllicll }las beenreverberating in society lately is still in tile pllase ofslogans being discussed and debated upon.ll1e concept GIld reali:=ation ofsuch a type oj"society still need to be clearlyformulated.TIle essence of that type oj" society is tltat it is denlocratic, upholds tile suprel1facy oflaw, e..\·tablj..\'lle..~· basic 11uman rig/lIs, develops science and tecJlno!o[!Y, aCCOJ11modate,.\· diversity, isenvironmentally oriented, and 110Ids belie,l'in (Jod.Its reallzati(}n require..\" re()rientations in educati()n especially in ternlS of tilecurriculum, instructional strategy, teac/1er-Iearner relation, and evaluation.